Pengaruh Limbah Organik terhadap Status Tropik, Rasio N/P serta Kelimpahan Fitoplankton di Waduk Panglima Besar Soedirman Kabupaten Banjarnegara - Endang Widyastuti; Sukanto Sukanto; Nuning Setyaningrum (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
The increased of organic substance pollutans in waters as one of stimulate factors for phytoplankton growth. The input of organic matter from antrophogenic activity tend to influence the trophic state of reservoir. The aims of this research are to examine the influence of organic waste to Panglima Soedirman reservoir concerning the trophic state, Redfield ratio N and P, also the relation with abundance of phytoplankton. This research used survey methods with purposive sampling technique on 7 obsevation stations with 3 repeating conducted on May-July 2013. The result of the research showed that the input of organic matter increased in BOD5, COD and ammonia in reservoir and trophic state. Redfield ratio was shown 19,13-65,82 which means P as a limiting factor. Relationship between N/P with the abundance of phytoplankton with degree was strong correlated with chlorophyta and chrysophyta.